Analysis of Promotion, Price, and Quality of Service to Interest in Visiting Tourists at The State Museum of Banten - Lina Aryani; Dewi Darmastuti; Ratna Hindria Dyah Pitasari; Desmintari Desmintari (Research Synergy Foundation, 2023)
The quality of service provided by the management of the Banten State Museum to visitors is an important factor in increasing satisfaction. The management of the Banten State Museum should be able to carry out appropriate promotion, marketing, and service strategies to attract more tourists in visiting. The goal of this study was to determine and identify promotion strategies, prices, and services that can influence tourist interest in Serang City, Banten. Population of this study are tourists who visit the tourist attractions of Serang City. This research method is the non-Probability sampling method, where not all populations have the same opportunity to become samples (prospective respondents). This study uses primary data obtained from questionnaires with a sample of 75 tourists visiting the tourist attractions of Serang City. Two kinds of data analysis are used in this research, namely descriptive analysis and PLS (Partial Least Square) analysis. The results showed that the magnitude of R Square (R2) Visiting Interest was 0.646. It means that promotion, price, and service quality factors contribute 64.6% of the influence on the interest of returning tourists. At the same time, the remaining 35.4% is influenced by other factors. This research concludes that the promotion factor, price factor, and service quality factor have a significant and significant effect on the interest of returning tourists to the Banten State Museum.